Single Center Experience With Veno-Venous Extracorporeal Membrane Oxygenation in Patients With Traumatic Brain Injury. Issue 6 (June 2021) - Parker, Brandon M.; Menaker, Jay; Berry, Cherisse D.; Tesoreiero, Ronald B.; O'Connor, James V.; Stein, Deborah M.; Scalea, Thomas M.
Veno-venous extracorporeal membrane oxygenation (VV-ECMO) use in patients following traumatic injury continues to increase. Some consider traumatic brain injury (TBI) as an absolute contraindication for VV-ECMO because of the concern for systemic anticoagulation (A/C) worsening intracranial injury. We evaluated outcomes and complications in patients with TBI treated with VV-ECMO. Methods: We retrospectively reviewed TBI patients ≥ 18 years of age treated with VV-ECMO. The primary outcome was survival to discharge. Secondary outcomes included progression of intracranial hemorrhage, bleeding complications, and episodes of oxygenator thrombosis requiring exchange. Medians and interquartile ranges were reported where appropriate. Results: 13 TBI patients received VV-ECMO support during the study period. The median age was 28 years (Interquartile range (IQR) 25-37.5) and 85% were men. Median admission Glasgow coma scale was 5 (IQR 3-13.5). Median injury severity score (ISS) was 48 (IQR 33.5-66). Median pre-ECMO PaO2:FiO2 ratio was 58 (IQR 47-74.5). Five (38.4%) patients survived to discharge. Six patients (46%) received systemic A/C while on ECMO. No patient had worsening of intracranial hemorrhage on computed tomography imaging. There were two bleeding complications in patients on A/C, neither was related to TBI. Four patients required an oxygenator change; 2 in patients on A/C. Conclusion: VV-ECMO appears safe with TBI. We have demonstrated that A/C can be withheld without increased complications. Traumatic brain injury should not be considered an absolute contraindication to the use of VV-ECMO for severe respiratory failure and should be decided on a case by case basis. Additional research is needed to confirm these preliminary findings.